2020
DOI: 10.1515/ijnes-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Nurse and midwife educators’ experiences of translating teaching methodology knowledge into practice in Rwanda

Abstract: ObjectivesThe aim of this study was to explore how nurse and midwife educators applied the knowledge and skills acquired from attending acontinuous professional development (CPD) workshop on teaching methodologies into their teaching practices in Rwanda.MethodsA qualitative descriptive design was used with a purposive sample of 15 nursing and midwifery faculty members from six private and public post-secondary schools in Rwanda. Participants were involved in semi-structured individual interviews. Inductive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Effective clinical practice in MMH requires nurse educators to be familiar with teaching strategies and the course to be taught so that they can teach effectively and provides students with current and evidence‐based information (Goh et al., 2021; Leonard et al., 2016). According to the review, most nurse educators lack confidence and competence in clinical teaching and mental health practice because of poor preservice preparation, as such they also fail to support students adequately (Gcawu et al., 2021; Legere et al., 2017; Ndayisenga et al., 2020; Vuckovic, Carlson, & Sunnqvist, 2021). The review has identified the need for training institutions to employ well‐trained teachers to support students in the classroom and clinical teaching (Yang & Chao, 2018).…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective clinical practice in MMH requires nurse educators to be familiar with teaching strategies and the course to be taught so that they can teach effectively and provides students with current and evidence‐based information (Goh et al., 2021; Leonard et al., 2016). According to the review, most nurse educators lack confidence and competence in clinical teaching and mental health practice because of poor preservice preparation, as such they also fail to support students adequately (Gcawu et al., 2021; Legere et al., 2017; Ndayisenga et al., 2020; Vuckovic, Carlson, & Sunnqvist, 2021). The review has identified the need for training institutions to employ well‐trained teachers to support students in the classroom and clinical teaching (Yang & Chao, 2018).…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…The study results indicate that both nursing colleges and teaching hospitals are under resourced in terms of skilled mental health educators and materials to support student teaching(Asirifi et al, 2017;Günaydin & Arguvanli Çoban, 2021;Ndayisenga et al, 2020). A severe shortage of skilled staff has led to students being used as a helping hand, and a shift in duties to non-specialized nurse educators, resulting in poor classroom presentation and students not fully understanding the content(Günaydin & Arguvanli Çoban, 2021;Ndayisenga et al, 2020;Yang & Chao, 2018). Findings also indicate that there are no guidelines for MMH competencies to standardize care and a lack of screening tools for MMH conditions(Adjorlolo et al, 2019;Brown et al, 2020).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Like other higher teaching and learning programs, nursing and midwifery education in Rwanda continues employing useful teaching methodologies that promote a conducive learning environment. [1][2][3][4] For example, to promote effective teaching and learning environment for their students and to reduce some challenges like continuing education during Covid-19 pandemic or continuing education while maintaining your working status and costs related to some other traditional teaching methods including money to travel to school and limited access to teaching and learning materials, both Rwandan private and public higher learning institutions (HLIs) initiated a blended learning (BL) approach in preservice nursing and midwifery education. [5] A BL approach combines the benefits of face-to-face and E-learning and minimizes the drawbacks of each method.…”
Section: Introductionmentioning
confidence: 99%